EFEKTIVITAS PEMBERIAN KOMPRES BAWANG MERAH TERHADAP PENURUNAN SUHU TUBUH PADA ANAK BALITA PASCA IMUNISASI DIWILAYAH KERJA PUSKESMAS MACCINI SAWAH - Fitri Anggraini K. Putri; Brajakson; Suhermi; Andi Mappanganro (CV. Adiba Aisha Amira, 2026)
Fever is one of the common side effects that often occurs in toddlers after immunization. Fever management is generally carried out with antipyretics, but non-pharmacological interventions such as shallot compresses can serve as an alternative due to their flavonoid and essential oil content, which have vasodilatory effects and improve blood circulation. This study aimed to determine the effectiveness of shallot compresses in reducing body temperature in toddlers after immunization at the working area of Maccini Sawah Public Health Center. This research employed a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of toddlers experiencing post-immunization fever, selected using purposive sampling. Temperature measurements were taken before and after the shallot compress intervention with a duration of 60 minutes. Data were analyzed using the paired t-test. The findings revealed a decrease in toddlers’ body temperature by an average of 1.2°C after the shallot compress intervention (p < 0.05), indicating significant effectiveness in reducing fever. Shallot compresses are effective in lowering body temperature in toddlers after immunization. This intervention can be considered a non-pharmacological alternative in the management of mild fever in children.